Post-transplant maintenance with blinatumomab for children, adolescents, and young adults with relapsed and refractory B-cell acute lymphoblastic leukemia: results of phase I in SCT-ALL-BLIN21 - Hirotoshi Sakaguchi; Kimiyoshi Sakaguchi; Itaru Kato; Hisashi Noma; Hidefumi Hiramatsu; Hiroyuki Ishida; Hiromasa Yabe; Hiroaki Goto; Yuta Kawahara; Yuka Iijima Yamashita; Masashi Sanada; Takao Deguchi; et al. (Haematologica)
Not available.